FAKTOR-FAKTOR YANG MEMPENGARUHI SKEPTISISME PROFESIONAL AUDITOR PADA KANTOR AKUNTAN PUBLIK DI SURABAYA - Rosdiana, Mega (Prodi Akuntansi FEB UNITOMO, 2020)
This study aims to examine the effect of independence, auditor skill, auditor experience, audit situation and time budget pressure on auditor professional skepticism. The population in this study are auditors from partner, senior, and junior levels who are work at public accounting firms (KAP) in Surabaya. Determination of the sample is determined by purposive sampling technique that is the selection based on the goal or target in choosing a sample not random (consideration of criteria) and relative can be compared with the results of previous studies. The independent variables in this study are the Independence variable, the Auditor Skill Variable, the Auditor Experience Variable, the Audit Situation Variable and the Time Budget Pressure Variable. The dependent variable is Professional Audit Skepticism. The data used are primary data by distributing questionnaires to auditors who work at the Public Accounting Firm (KAP) in Surabaya. The results are independence, auditor skill, the audit situation does not affect auditor skepticism, while audit experience and time budget pressure affect auditor skepticism.